Looking at the Changes of Writing Materials in Italian Medieval Records - Marta Luigina Mangini (HyperCultura, 2014)
Abstract Recently, the methodological approach that has developed regarding the double historicity of the texts, the duality - material and content - inside each of them, has allowed the overcoming of the opposition between “the pureté de l'idée et sa corruption par la matière” (Chartier). To fully understand the meanings of texts, it is crucial to study their material aspects. The moment, the place, the writers, but also the purpose, the content, the authors and the recipients of a text profoundly affect the exterior forms of a record, starting from the choice of writing materials. Just now, when the space of writings is becoming immaterial, it is important to consider the causes and consequences of past changes of writing surfaces and their impact on the most widespread and preserved materials. Analyzing these changes, studying their causes and effects, the quantitative and qualitative progresses of the different materials used, helps us understand memory and the present of our cultural heritage.